2001
DOI: 10.1001/archinte.161.7.929
|View full text |Cite
|
Sign up to set email alerts
|

Report of the Council on Scientific Affairs

Abstract: Needlestick injuries continue to pose a significant risk to health care workers; however, appropriate use of needlestick prevention devices, especially in comprehensive prevention programs, can significantly reduce the incidence of such injuries. Cost analyses indicate that use of these devices will be cost-effective in the long term. To provide more scientific and cost data on the efficacy of needlestick prevention devices, recording of needlestick injuries must be improved. Federal law now requires the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(7 citation statements)
references
References 27 publications
3
3
0
1
Order By: Relevance
“…Nurses reported most needlestick and sharp injuries. This is in accordance with reports from other countries [3], [4]. Incidence of PEIs is likely related with usage of sharp instruments and nurses may be more likely than doctors (except surgeons, perhaps) to be handling sharps.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nurses reported most needlestick and sharp injuries. This is in accordance with reports from other countries [3], [4]. Incidence of PEIs is likely related with usage of sharp instruments and nurses may be more likely than doctors (except surgeons, perhaps) to be handling sharps.…”
Section: Discussionsupporting
confidence: 91%
“…According to the Centers for Disease Control and Prevention (CDC) approximately 600,000 health care workers in the United States experience exposures to blood each year [3]. These may occur in the emergency departments, in the operating room, in the radiology or other departments and may be related to faulty needle insertion techniques, needle recapping, or incautious disposal of contaminated needles and sharps [2], [4], [5]. Needlestick and sharp injuries may be combined with failure to use appropriate barrier garments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, majority of NSIs were reported by staff nurses, (42.9%), which is a similar result compared with previous studies (4,6,(13)(14)(15)(16). This incidence rate is high though compared with a study done by Jayanth et al (17), where 28% of nurses had experienced NSIs.…”
Section: Discussionsupporting
confidence: 92%
“…Using needle protective devices or double gloving may be cost effective in the long term [14], with a additional 5% cost and 6% cost saving having been reported [15]. However, there is a need for undertaking more cost-effective analysis to determine further validation.…”
Section: Introductionmentioning
confidence: 99%